Is Special Education Teaching in Ireland Stressful? Coping with Work-related Stress - Doyle Bradley, Natalie (TARA, 2021)
This article explores the concept of work-related stress amongst Special Education Teachers in Ireland. The aim of this research was to identify if work-related stress exists among SETs, and if it does exist, capture baseline data describing the issue. Using an exploratory mixed-methods approach, qualitative data was collected utilising a guided journaling group who explored personal accounts of WRS from Irish SETs in a range of settings.
Journal article
Keywords: Special Education Teaching (SET); Work related stress; Ireland; Job stress; Education